Activist theology - Henderson-Espinoza, Robyn (Fortress Press, 2019)
In this searing and personal book, Robyn Henderson-Espinoza bridges the gap between academia and activism, bringing the wisdom of the streets to the work of scholarship, all for the sake of marginalized communities. This interdisciplinary work draws on continental philosophy, queer theology, and critical class theory in accessible and artful ways that explain the project of activist theology. It breaks new ground and summons all to radical acts of labor to build bridges with difference.